CONTINUITY OF REHABILITATION CARE BETWEEN HEALTH CONTEXTS: CASE STUDY - Rui Pedro Silva; Elisabeth Sousa (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Objective: To describe, from the perspective of continuity of care, a clinical case where there has been monitoring by rehabilitation nurses for a year, involving different contexts of health care provision. Materials and method: The case reports to a patient with multimorbidity, who has been the target of health care in four different contexts over the past year: ECCI, acute hospital admission, maintenance / rehabilitation hospital admission and ambulatory. In each of the described contexts, the user was subject to an assessment by the rehabilitation nurse, which resulted in the implementation of a rehabilitation plan whenever the clinical condition allowed. In each of the isolated contexts, there was a positive functional and / or clinical evolution, which translates into significant evolution when comparing the chronological extremes of the period in question. Between each different context, there was formal and informal communication of clinical data, including the rehabilitation plan underway at the time of the transition between contexts. Results and discussion: From the analysis of the exposed data, it is possible to make the following inferences: a) there was a positive evolution of the user's functional condition between the beginning and the end of the period under analysis (total recovery of muscle strength, balance and autonomy of the users). self-care); b) in each individual context, and whenever the patient's clinical condition allowed, a specific rehabilitation plan was implemented, which resulted in functional and clinical gains; c) although there was formal and informal communication between contexts about the rehabilitation plan, a unique and dynamic rehabilitation plan was not followed; d) possibly, a unique and dynamic rehabilitation plan would allow to achieve the results obtained more quickly, due to the greater fluidity of care between contexts. Conclusion: It is possible to have long-term rehabilitation strategies in complex clinical cases, even if several contexts of health care provision come into equation. Although the communication between the different contexts allows the sequencing of the respective rehabilitation plans, there is room for improving the continuity of care between different services and the ambition is to adopt a single, transversal and dynamic rehabilitation plan; a possible way for this improvement will be the formalization of direct communication between its professionals, as a complement to the use of the information systems in use.